Sensitivity of photovoltaic cells efficiency to initial conditions in various aggregation designs - Baharak Mohamad Jafari Navadel; Esfandyar Faizi; Baharam Ahansaz; Jaber Jahanbin Sardroodi (Results in Physics)
It is thought that nature already exploits quantum mechanical properties to increase the efficiency of solar energy harvesting devices. Thus, the operation of these devices can be enhanced by clever design of a nanoscopic, quantum mechanical system where the quantum coherence plays a crucial role in this process. In this investigation, we develop a donor–acceptor two level trap dipole model converging the key role of quantum coherence and aggregation effects along with different initial states. Our analysis reveals that quenching unwanted emissions is achievable by preparing the system in specific initial state under the effect of optimal spatial aggregation. Interestingly it is observed that characterizing aggregation-induced properties and quantum effects of bandgap engineering can increase the power enhancement up to 35.87% compared with classical counterparts. This encouraging trend suggests a promising novel design aspect of nature-mimicking photovoltaic devices.